ANGGARAN PEMERINTAH DAERAH DALAM BINGKAI AMIN, AMAN, UMAN: SEBUAH STUDI SEMIOTIKA BARTHESIAN - Anjang Pranata; Gugus Irianto; Noval Adib (Universitas Negeri Malang, 2018)
This study aims to reveal the meaning of local government budget. The paradigm used in this research is interpretive by using Barthesian Semiotics research method. Semiotics Barthesian emphasizes the relationship between the sign with the individual experience and the culture of its users. Roland Barthes's ideas include the meaning of denotation, connotation and myth. The results reveal that the meaning of denotative local government budget is a plan embodied in monetary units. While the connotative meaning of local government budget is the result of agreement between the executive and legislative (amin). The preparation, execution, and reporting of the budget must comply with the prevailing laws and regulations (aman). Budgets are used to meet executive and legislative interests (uman). At the level of mythical budget is identified as an effort to welfare the community.